MOTIVASI PARK GEUN-HYE MENERAPKAN KEBIJAKAN TRUST POLITIC DALAM MENGHADAPI KOREA UTARA PADA TAHUN 2013-2016 - Siska Ayu Anggraini; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research is explanatory research which aims to explain why Park Geun-hye applied the Trust Politic policy in dealing with North Korea in 2013-2016. Park Geun-hye was the president who was elected in the South Korean presidential election on December 19, 2012 for the 2013-2018 term of presidency. Known as the first female president in the country, park also has an attractive background as former president Park Chung-hee's daughter. Kim Dae Jung's Sunshine Policy failure and Lee Myung Bak's isolation policy made the South Koreans very vulnerable to the North Korean issue during the election period. From here, Park Geun-hye came up with a policy that was felt as a breath of fresh air and suitable for South Korea towards North Korea, namely Trust Politic policy.The author uses the perspective of behavioralism, which is supported by Richard Snyder's decision making theory and foreign policy concepts at the level of individual analysis as the main actor in international relations. This research uses qualitative methods and literature studies as sources of information.The results of this study show the reason of Park Geun-hye implemented the Trust Politic policy towards North Korea in 2013-2016 was influenced by internal and external factors. Internal factors are Park Geun-hye's idealistic and progressive perception of North Korea and the failure of foreign policy towards North Korea before Park's time. While external factors are an escalation of threats from North Korea which is increasingly alarming and support from the international community towards Trust Politic policies.Keyword: Park Geun-hye, Trust Politic, Foreign Policy, North Korea